2021
DOI: 10.1210/clinem/dgab669
|View full text |Cite
|
Sign up to set email alerts
|

Myopia and Early-Onset Type 2 Diabetes: A Nationwide Cohort Study

Abstract: Objective A correlation between myopia and insulin-resistance has been suggested. We investigated the association between myopia in adolescence and type 2 diabetes (T2D) incidence in young adulthood. Design Population-based, retrospective, cohort study. Methods 1,329,705 adolescents (579,543 women, 43.6%) aged 16-19 years, medically examined before mandatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…The changes of hyperglycemia in lens are recognized to cause myopia. 2527 Similarly, our study suggested diabetes was to be a risk factor of myopia. Furthermore, diseases such as hallux valgus, osteoarthritis, hernia, diverticular disease/diverticulitis, joint disorders, ventral hernia, Stickler syndrome, Donnai-Barrow syndrome, and diverticular disease/diverticulitis were also found to have causal impacts on myopia.…”
Section: Discussionsupporting
confidence: 63%
“…The changes of hyperglycemia in lens are recognized to cause myopia. 2527 Similarly, our study suggested diabetes was to be a risk factor of myopia. Furthermore, diseases such as hallux valgus, osteoarthritis, hernia, diverticular disease/diverticulitis, joint disorders, ventral hernia, Stickler syndrome, Donnai-Barrow syndrome, and diverticular disease/diverticulitis were also found to have causal impacts on myopia.…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, in a recent study using this database, we demonstrated that adolescent women with myopia were at a significantly increased risk for incident type 2 diabetes in young adulthood in a severitydependent manner [44].…”
Section: Discussionmentioning
confidence: 85%
“…Notably, among individuals with primary growth hormone receptor insensitivity (Laron syndrome), the mean ocular axial length was significantly longer in those treated than not treated with supplemental IGF‐1 (22.53 [0.81] vs. 21.94 [1.74] mm) [36]. Moreover, in a recent study using this database, we demonstrated that adolescent women with myopia were at a significantly increased risk for incident type 2 diabetes in young adulthood in a severity‐dependent manner [44].…”
Section: Discussionmentioning
confidence: 99%